Estudo do biochar de borra de café no tratamento do lixiviado do aterro sanitário de Campo Mourão - Sousdaleff, Martha (2024)
Urban growth, population increase, and consumerism have led to the accumulation of municipal solid waste (MSW), causing serious problems due to improper disposal, especially in open dumps. These sites, often poorly managed, contaminate soil, air, and groundwater, promoting the spread of diseases. Sanitary landfills emerge as the recommended solution, providing efficient treatment through soil impermeabilization, leachate drainage, and gas capture. In Brazil, the National Solid Waste Policy (PNRS) requires the replacement of open dumps with sanitary landfills, ensuring proper waste treatment and avoiding penalties and restrictions on federal funds. Leachate, a byproduct of waste decomposition, presents significant challenges for treatment due to its complex composition, making the development of new solutions necessary. In this context, coffee grounds, rich in carbon, stand out as a promising alternative for the production of biochar, which has shown effectiveness in reducing leachate contaminants, aligning with the Sustainable Development Goals (SDGs), particularly SDG 6, which aims to improve water quality and sanitation. Research conducted on the leachate from the Campo Mourão landfill shows that the L1 pond (raw leachate) has a significantly higher pollutant load in parameters such as color, turbidity, conductivity, phosphorus, and nitrates, suggesting different stages of waste degradation. In contrast, the L2 pond (treated leachate) showed considerably lower results, indicating effective treatment. Chemically activated biochar demonstrated high rates of color reduction (between 61.9% and 94.4%) and efficiency in turbidity reduction, ranging from 49% to 92.2%. The bioassay with Allium cepa revealed that coffee grounds biochar mitigated the cytotoxicity and genotoxicity of the leachate. Statistical analysis indicated that the adsorbent mass and pollutant concentration significantly influence reduction efficiency, suggesting that optimizing experimental conditions may result in further improvements. Spectroscopic and microscopic analyses confirmed the effectiveness of biochar and activated carbon in adsorbing pollutants, highlighting their potential as sustainable solutions for leachate treatment.